Morality : reasoning on different approaches - Gluchman, Vasil. (Value Inquiry Book Series, 2013)
This book of essays focuses on the new approaches to moral issues from two perspectives. The first part, 'Various Concepts of Morality', analyses certain central approaches to moral study, and creates the methodological starting point for the more specific enquiries of the second part. 'New Trends in Understanding Morality' contains five articles focusing on these new approaches, especially as they are related to their conceptions of scientific knowledge. This section deals with selected special issues of morality in biology, natural sciences, but also in humanities.